Individual risk factors predictive of venous thromboembolism in patients with temporary lower limb immobilization due to injury: a systematic review. (7th February 2019) - Horner, Daniel; Pandor, Abdullah; Goodacre, Steve; Clowes, Mark; Hunt, Beverley J.
Abstract : Essentials Thromboprophylaxis after lower limb injury is often based on complex risk stratification. Our systematic review identified variables predicting venous thromboembolism (VTE) in this group. Age and injury type were commonly reported to increase the odds of VTE (odds ratio 1.5–3.48). We found limited evidence to support the use of other risk factors within prediction models. Summary: Background: Patients immobilized after lower limb injury are at risk of venous thromboembolism (VTE). There is international variation in the use of thromboprophylaxis for such patients. Risk‐based strategies have been adopted to aid decision making in many settings. The accuracy of these strategies is unclear. Objectives: A systematic review was undertaken to identify all individual patient‐identifiable risk factors linked to any VTE outcome following lower limb immobilization. Methods: Several electronic databases were searched from inception to May 2017. Any studies that included a measurement of VTE as a patient outcome in adults requiring temporary immobilization (e.g. leg cast or brace in an ambulatory setting) for an isolated lower limb injury and reported risk factor variables were included. Descriptive statistics and thematic analysis were used to synthesize the evidence. Results: Our database search returned 4771 citations, of which 15 studies reporting outcome data on 80 678 patients were eligible for analysis. Risk‐factor associations were reported through regression analyses, non‐parametric tests and descriptive statistics. All studies were assessed as at moderate or serious risk of bias using the ROBINS‐I risk of bias tool. Advancing age and injury type were the only individual risk factors demonstrating a reproducible association with increased symptomatic and/or asymptomatic VTE rates. Several risk factors currently used in scoring tools did not appear to be robustly evaluated for subsequent association with VTE within these studies. Conclusions: Clinicians should be aware of the limited evidence to support individual risk factors in guiding thromboprophylaxis use for this patient cohort.